Chitooligosaccharides display anti-tumor effects against human cervical cancer cells via the apoptotic and autophagic pathways. (15th November 2019) - Zhao, Mengyao; Gu, Liming; Li, Yun; Chen, Shumin; You, Jiangshan; Fan, Liqiang; Wang, Yudong; Zhao, Liming
Graphical abstract: Highlights: High-degree-polymerized COS were obtained by enzyme-membrane coupling reactor. COS treatment of C33A cells induced ROS production and decreased the MMP. COS treatment induced cell apoptosis and regulated apoptotic-related proteins. COS treatment increased the levels of autophagy markers. Abstract: Gynecological cancers are the most commonly diagnosed forms of cancer among the female population. Chitooligosaccharides (COS)—hydrolysis products from chitosan—display high bioavailability, high water solubility, and low molecular weight properties. Here, we investigated the influence of COS on 11 gynecological tumor cell types, and subsequently elucidated molecular mechanisms through which the observed inhibition occurred. Initially, we used a controllable enzyme-membrane coupling reactor system to obtain COS with a high degree of polymerization; the yield of high-degree-polymerized COS (DP 5–12) obtained with this reactor system accounted for ∼75% yields (w/w). Using these COS materials, cell line assays showed that COS elicited the most significant anti-tumor activity against C33A cells, with anti-tumor mechanisms related to oxidative stress, as well as activation of intrinsic mitochondrial apoptosis and autophagic signaling. Thus, we provide experimental evidence to demonstrate how the enzyme-membrane coupling reactor system can generate COS that exert bioactivity against gynecological cancers.